15N/14N stable isotope ratios changes during nitrate reduction in a soil - Marina PINTAR (Acta Agriculturae Slovenica, 2002)
Seven days continuous incubation experiment in anaerobic condition with undisturbed samples from four soil depths (10-20 cm, 30-40 cm, 50-60 cm, 90-100 cm) was performed for observing nitrate reduction and nitrate nitrogen isotopic composition changes (?15N). Soil was incubated at the temperature of 9° and 18°C. Nitrate was added in equivalent amount of 63.8 kg N-NO3/ha for the uppermost soil layer. In one of the three variants glucose was added in the equivalent amount of 140 kg C/ha. The isotope measurements of nitrate nitrogen in soil water proved the nitrate reduction process (presumably denitrification) in the anaerobic soil column system, where nitrate concentration measurement alone did not prove this process. The isotopic separation factors (?), calculated with Rayleigh formula for nitrate reduction in water in soil columns were –6.67 ‰, what shows high denitrification rate in the uppermost horizon and –34.20 and –36.18 ‰, what shows slow process in the parent soil material.